Collective Impact through Public Health and Academic Partnerships: A Kentucky Public Health Accreditation Readiness Example - Carman, Angela L. (Frontiers in Public Health, 2015)
In the ever-changing, resource limited public health environment, the use of partners can provide training, consultation and technical assistance needed to increase local health department workforce capacity to meet new public health demands including national public heath accreditation. This manuscript describes the provision of the backbone support activities of facilitation, data management and project management by UKCPH to Kentucky’s local health departments seeking national public health accreditation.